Recreational sports activity on gross motor skill among grassroot level children – A pilot study - Ramesh, K.A.; Ramakrishnan, R. (University of Jaffna, 2022)
Grassroots sport teaches how youths to lead healthy lifestyles early in their life and how to continue participating in recreational activities throughout their life. The aim of this pilot study focuses to develop fundamental gross motor skills through the influence of recreational sports activity from the grass root level. To achieve the purpose forty (n=40) Grassroot level children were randomly selected from Sacred Heart higher secondary school, Tiruchirappalli, Tamil Nadu, India. The participants’ age ranged from five to six years. The selected participants were divided into two groups of twenty participants each namely the experimental and control group. The experimental group underwent six weeks of recreational sports activity program and the control group underwent regular activity. The Gross Motor skills (Such as Locomotor and object control skills) were selected as dependent variables. To test the Gross motor skill the Gross motor quotient score was taken from the Test for Gross motor development – 2 test (TGMD-2) were used. The collected data on the selected variables were treated with paired sample “t” test to find the improvement between the pre and post-test and ANCOVA to find out the improvement difference between the groups at 0.05 level of significance. The result of the study revealed that the experimental group significantly improve gross motor skills (t=10.23) than the control group. Hence it was concluded that the experimental group had a significant improvement difference in gross motor skills (F=88.81) among Grassroot level children than the control group.
Keywords: Recreational Sports activity; Gross Motor Skill; Grassroot level children